Effect of Sundanese music on daytime sleep quality based on EEG signal - Kusumandari, Dwi Esti; Suhendra, Muhamad Agung; Rizqyawan, Muhammad Ilham; Simbolon, Artha I.; Turnip, Arjon; Wardono, Prabu; Rizka, Adriani (AIP conference proceedings, 2019)
In theory, Daytime sleep is decreasing stress and increasing mood, focus, cognitive function. In this research, we would like to know the impact of Sundanese music on sleep quality based EEG signals in the daytime. The extraction features used wavelet Daubechies D8 level 7 and Fast Fourier Transform to divide it to alpha and theta band ranges. The experimental results from 10 subjects showed that using Sundanese music as treatment can make brain activity become calm and relax. Also, using T-Test to find relationships and influences between pre and post-treatment and The Result of T-Test showed that the value (p) is below 0.05 (p< 0.05), then these treatment has affected and it can to be alternative for day time sleep therapy.